The Legal Study of Electronic Contracts in Buying Selling based on the Legal System in Indonesia - Aryani Witasari (JURNAL AKTA, 2022)
The current development of contract law is no longer limited to contract agreements made conventionally, but has developed in contract agreements made electronically. The purpose of this study is to analyze the position of electronic contracts based on the legal system in Indonesia. The research method used is through a normative juridical approach by describing and analyzing the results of the research qualitatively in relation to the laws and regulations that form the basis of the study. The results of the discussion show that the contract law system in Indonesia adheres to an open system based on the principle of freedom of contract. Everyone is free to enter into an agreement in any way and regardless of its form, as long as it fulfills the requirements for the validity of the agreement as stipulated in the provisions of Article 1320 of the Civil Code. Contracts made electronically by the parties, as long as they comply with the provisions of Article 1320 of the Civil Code, remain valid. One problem that often arises is proving the existence of an agreement between the parties, because in contracts made electronically, the original signatures of the parties are usually not attached.